Kepedulian Keamanan Informasi di Pemerintahan: Praktik Manajemen dan Dampaknya - Bemy Fachriandi; Teduh Dirgahayu (Jurnal Manajemen Informatika (JAMIKA), 2021)
Currently the organization is facing challenges due to the Covid19 pandemic which has caused changes in work patterns for all members of the organization. The priority of management is to give more attention to information security, especially for members and government organizations in general. Various information security practices have been carried out, but there are obstacles that occur such as the lack of awareness of information security, work behavior, work culture, and the lack of human resources available and this can have a negative impact on the level of information security concern in the organization. Information security practices carried out by management do not always have an impact on changes in the behavior of organizational members. From the data obtained, there are many information security practices that may have been implemented by management. But do members of the organization care about the practice. Therefore, it is important to conduct research with the aim of knowing the practice of information security concern that has been carried out by management whether it has an impact on organizational members, especially the organization itself. This study used qualitative and quantitative interpretive approaches as a data collection process in three government organizations. Qualitative is used to obtain data from management and processed using the SAP-LAP model through interviews. Then an online survey was conducted with members of the organization to determine the impact of implementing information security care practices on the organization. The results show that organizational members have a high level of concern for the management's information security practices.